2018
DOI: 10.1002/fuce.201700233
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method of Synthesizing Boron‐doped Carbon Catalysts

Abstract: Boron‐doped carbon catalysts are prepared by a novel method combining hot filament chemical vapor deposition technique with high temperature annealing treatment. Nano‐boron powders are coated by thin diamond layers and then the coated nano‐boron powders are annealed for different times at 1,300 °C in vacuum. The morphology, microstructure, and chemical bonding states of the synthetized materials have been investigated by scanning electron microscope (SEM), X‐ray diffraction (XRD), Raman spectroscopy, Fourier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, the ORR catalytic activity of BCNTs was lower than that of commercial Pt/C catalysts and even lower than that of NCNTs catalysts under acidic conditions. Suo et al made boron-doped carbon catalysts by chemical vapor deposition and high-temperature annealing [68]. As shown in Figure 8b,c, FTIR and XPS showed that, after annealing for 2 h, the boron content was directly proportional to the Compared to those of NCNTs catalysts, the stability and CO toxicity resistance of BCNTs catalysts were also good.…”
Section: Boron Dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the ORR catalytic activity of BCNTs was lower than that of commercial Pt/C catalysts and even lower than that of NCNTs catalysts under acidic conditions. Suo et al made boron-doped carbon catalysts by chemical vapor deposition and high-temperature annealing [68]. As shown in Figure 8b,c, FTIR and XPS showed that, after annealing for 2 h, the boron content was directly proportional to the Compared to those of NCNTs catalysts, the stability and CO toxicity resistance of BCNTs catalysts were also good.…”
Section: Boron Dopingmentioning
confidence: 99%
“…( c ) Survey scanning XPS spectra of the deposits annealed for (i) 1, (ii) 2 and (iii) 3 h, respectively. High-resolution XPS spectra for the B 1 s peak of the deposits annealed for (iv) 1 and (v) 2 h, respectively [ 68 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation